Towards Idea Generation for Fashion Product Design and Development in Bangladeshi Industry - Chowdhury, Sutapa (European Scientific Journal, ESJ, 2019)
New Product Development (NPD) has always been one of the most significant components for the fashion industry. Research has shown that investments in design can lead to the development of completely new trends or can transform an existing trend in such a way that can offer newer aspects in the industry in general. However, there is insufficient evidence on the most appropriate or effective role that design could play in the real-life scenario. Previous case-based research has identified alternative roles for designers in NPD, but there is only tentative evidence over such roles’ contribution to NPD outcomes. By using data on a large sample (c. 1300) of Irish manufacturing plants Bangladesh is now able to examine the effectiveness of three different levels of involvement of designers in NPD and their impact on NPD novelty and success. This analysis suggests that design is closely associated with enhanced performance regardless of the type of role it plays. However, from a practical point of view, the potential effects of involving design throughout the process appear to be much greater. It is important to note here that the relationship between design and NPD outcomes is also strongly moderated by contextual factors; for example, its significance is only evident for organizations which also engage in in-house R&D. Also, while both small and larger plants do gain from using design as functional specialism and in some stages of the NPD process, the additional benefits of a continuous involvement of design throughout the process are only evident in larger plants. Finally, while discourse and perceptions over design’s role in NPD has certainly changed over time, suggesting a much more widespread and strategic use of design, providing a more static picture, showing that design engagement with the NPD process has not changed significantly over the last two decades.